THE RELATIONSHIP BETWEEN JOB SATISFACTION AND CREATIVITY AMONG TENNIS TEACHERS IN THE UNIVERSITIES OF THE MIDDLE EUPHRATES - Abdulaziz Muhammad, Dr. Manaf; Jawad Al-Saegh, Dr. Ali Mohammed (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
Major developments have occurred in management in recent years, and these developments came as a result of technological progress in all areas of life. It has become necessary for any organization to keep pace with these developments in order to be distinct from other organizations similar to it in the nature of its work. To achieve this requires preparing leaders capable of using. The application of modern management methods, and this in turn requires the availability of good awareness and awareness to create suitable job satisfaction for working individuals. Through his knowledge of the sports movement in the country in general and racket games in particular, the researcher wanted to study one of the important administrative aspects that is taken into account when judging the progress and advancement of nations, and that any administrative method It depends on the efficiency of the ability to deal with mathematical problems, job satisfaction, legal knowledge, and creativity are linked and interactive with each other and affect each other. The process of job satisfaction is a vital and important process, which consequently leads to creativity at work.